Diabetic Patients’ Practices Towards Prevention of Diabetic Foot Ulcers in Ribat University Hospital - Susan Zroog; Fatima Elhag Ahmed; Yassin Nor-Aldaiem; Abdelhakam Ali (AlQalam Journal of Medical and Applied Sciences, 2025)
Diabetic foot ulcers are among the most common side effects of diabetes mellitus and are associated with a high morbidity and death rate in diabetic patients. If diabetes is not treated and managed properly, diabetic foot ulcers can result in disability and even death. To prevent this condition, the patient should be knowledgeable about diabetic foot self-care and have enough practice with it. A descriptive study aimed to assess the practices of adult diabetic patients regarding the prevention of diabetic foot ulcers at Ribat University Hospital’s follow-up clinic. The sample consisted of 80 diabetic patients who constituted all available patients during February 2023. Data was gathered through structured interview questionnaires and inputted and analyzed with the Statistical Package for Social Sciences (SPSS). In this research, a total of 80 patients participated, 45% were males. 50% of patients with a disease duration of 1-10 years. According to the results of this study, the overall mean of practice was 45.75%, which means patients had a low level of practice towards the prevention of diabetic foot ulcers. The overall mean of practices concerning the prevention of diabetic foot ulcers was inadequate. Increasing patient awareness with education on appropriate foot self-care is very important. تُعد قرح القدم السكرية من أكثر الآثار الجانبية شيوعًا لمرض السكري، وترتبط بإرتفاع معدلات الإعتلال والوفيات لدى مرضى السكري. إذا لم يُعالَج داء السكري بشكل صحيح، فقد تُؤدي قرح القدم السكرية إلى الإعاقة وحتى الوفاة. للوقاية من هذه الحالة، يجب أن يكون المريض على دراية بالعناية الذاتية بالقدم السكرية وأن يمتلك خبرة كافية في ذلك. هذه الدراسة الوصفية اجريت لتقييم ممارسات مرضى السكري البالغين في عيادة المتابعة بمستشفى الرباط الجامعي فيما يتعلق بالوقاية من قرح القدم السكرية، وتألفت العينة من (80) مريضًا مصابًا بمرض السكري، والذين شكلوا جميع المرضى المتاحين خلال شهر فبراير 2023. جُمعت البيانات من خلال استبيانات، وتم إدخال البيانات وتحليلها باستخدام الحزمة الإحصائية للعلوم الاجتماعية (SPSS). شارك في هذا البحث 80 مريضًا، 45% منهم من الذكور. 50٪ من المرضى الذين تتراوح مدة مرضهم بين 1 و10 سنوات. ووفقًا لنتائج هذه الدراسة، بلغ المتوسط ​​العام للممارسة 45.75 ٪، مما يعني أن مستوى ممارسة المرضى للوقاية من قرح القدم السكرية منخفض. وكان المتوسط ​​العام للممارسات المتعلقة بالوقاية من قرح القدم السكرية غير كافٍ، لذا فإن زيادة وعي المرضى بأهمية العناية الذاتية بالقدم أمر بالغ الأهمية